Progress and gaps in childhood immunization among two-year-olds in Ghana (1993–2022): A trend and equity analysis - Florence Gyembuzie Wongnaah; Augustus Osborne; Khadijat Adeleye; Bright Opoku Ahinkorah (PLoS ONE, 2026)
Background Immunization remains a cornerstone of child survival and population health. While Ghana has made significant strides in vaccine delivery over the past three decades, gaps in equitable and universal coverage persist. This study examined the progress and gaps in full immunization coverage among two-year-olds in Ghana from 1993 to 2022. Methods We used data from the Ghana Demographic Health Survey rounds conducted between 1993 and 2022 to examine full immunization coverage among two-year-olds. Disaggregated data were accessed via the WHO Health Equity Assessment Toolkit (HEAT). Inequality was assessed across six dimensions: maternal age, household wealth status, maternal education, place of residence, child’s sex, and subnational region. Various inequality measures, including difference, ratio, population-attributable risk, and population-attributable fraction were calculated. Results Full immunization coverage improved from 55.5% in 1993 to 71.5% in 2022, peaking at 77.6% in 2008. Inequality analysis showed reduced socioeconomic disparities related to wealth, maternal education, and urban-rural residence by 2022. However, two key inequalities persisted: maternal age-related inequality significantly widened to 26.8 percentage-point gap in 2022 between mothers aged 20–49 and adolescent mothers (15–19 years), and substantial regional disparities remained, with a significant 39.8 percentage-point gap between the best- and worst-performing regions. Conclusion Despite the gains in full immunization coverage in Ghana over the past three decades, significant inequalities persist, particularly among adolescent mothers and populations in disadvantaged regions. Strengthening equity-focused immunization strategies is essential to achieving universal coverage.